Prevalence of gastrointestinal helminthiasis in goats and sheep in the central region of Rondônia (Research, Society and Development, 2025)
The high prevalence of gastrointestinal helminth infections represents one of the main sanitary and productive constraints faced by goat and sheep producers. This study aimed to evaluate the occurrence and intensity of these infections in goats and sheep from rural properties located in the central region of Rondônia, Brazil. Fecal samples were collected from 114 animals across five different farms. Analyses were performed using the McMaster technique to quantify eggs per gram of feces (EPG), followed by coproculture for the identification of L3 larvae. The results revealed a prevalence of 76.3% of animals infected with gastrointestinal nematodes. Among the L3 larvae identified, Haemonchus spp. predominated (77,7%), followed by Trichostrongylus spp. (17,4%), Oesophagostomum spp. (3.2%), Trichuris spp. (1.2%), and Strongyloides spp. (0.6%). The predominance of Haemonchus contortus is particularly concerning due to its high pathogenic potential, which leads to significant productive losses and discourages the continuity of the activity.